Gender Affirmation Surgery of the Face for the Transfeminine Patient - Donaldson, Lane; Wulu, Jacqueline; Garcia-Rodriguez, Laura (Facial Plastic Surgery, 2023)
This article discusses the aspects of facial feminine affirmation surgery including forehead reconstruction, midface feminization, and lower face/neck feminization. We will present a brief history of gender affirmation. We discuss the anatomical differences between born XY males and XX females and discuss the subsequent procedures that aim at feminizing the face. The effects of silicone injections are also discussed as this was a trend in the past to feminize the face. Understandably so we discuss the anatomical differences as being a fluid expression and differences based on ethnic background.
Keywords: facial affirmation; facial feminization surgery; forehead reconstruction; rhinoplasty; cheeks; body dysmorphic disorder; gender dysphoria